العلاقة بين أجنحة المرضى والأشكال المعمارية - رضوان الطحلاوي; بول شنيارة; محمد سفيان كوراني; محمد كيخيا (Tishreen University, 2019)
ارتبطت أجنحة الإقامة في المستشفيات من الجانب التصميمي بمجموعة أشكال سبغت مسقطها الأفقي بشكل عام، وأصبحت في معظم الأحيان نماذج شائعة مرغوباً اعتمادها عند تصميم تلك الأجنحة. ولما كان تناول (الشكل) كمصطلح، أو الحديث عنه، يثير مؤيدي ومعارضي مدرستي (الوظيفية) و(الشكلية) المعماريتين، فإن هذا البحث ضروري وهام للتعريف بالأشكال التكوينية المستعملة في تصميم المسقط الأفقي لأجنحة إقامة المرضى في المستشفيات، وكيف أصبحت بذلك الحضور؟ كما يسعى لتبيان فيما إذا كانت تعود بانتمائها إلى الشكلية المعروفة، أو أنها نتاج تطور مبني على ما يعرف بعلم التشكل Morphology وقواعده. وسيتناول البحث بالإضافة لذلك، مدى تضمن هذه النماذج الشكلية في تطبيقاتنا المحلية، وذلك من خلال رصد ميداني للنماذج المعتمدة في تصميم أجنحة مستشفياتنا السورية. From the designing side, the horizontal plan of hospital wards is associated with a number of forms that dominate it.  Generally speaking, these forms have become commonly desired models in designing hospital wards. However, since dealing with or discussing "forms" as an idiom stimulates both the proponents and opponents of the architectural schools of Formalism and Functionalism, this research is relevantly necessary for explaining these forms. This has been achieved by introducing and describing why they have become existent in the contemporary architectural environment, on the one side, and how they identify the extent to which they are related to either formalism, or to the process of natural historical development built on scientific rules of Morphology. Furthermore, the research discusses the implications of these forms through the ward designing of the Syrian hospitals.